Incidental hepatic steatosis in radiology reports: a survey of emergency department clinicians' perspectives and current practice. Issue 5 (5th August 2019) - Kutaiba, Numan; Rotella, Joe‐Anthony; Ardalan, Zaid; Testro, Adam
Abstract: Introduction: Hepatic steatosis is a relatively common incidental finding on computed tomography (CT) studies performed for patients in the emergency department (ED). The aim of our survey was to explore the preferences and perspectives of emergency physicians regarding reporting of incidental findings with a focus on hepatic steatosis. Methods: A prospective web‐based questionnaire was conducted and distributed electronically to emergency clinicians with anonymous collection of responses. Results: A total of 236 responses were received. The true response rate could not be determined due to different methods of electronic distribution. However, there was an estimated representation of 8.3% for ED physicians and 2.5% for trainees. The median time spent on the survey was less than 3 minutes. Seventy‐seven per cent answered yes to giving an incidental finding more significance if mentioned in the conclusion section. More than half of respondents (60.2%) reported that they would like hepatic steatosis to be mentioned in a CT report while 30% reported that it was irrelevant in the emergency setting and 10% reported that they did not want it mentioned in the report. The majority (83.1%) reported that they would include this finding in the discharge summary for GP follow‐up and less than half (44.1%) would mention it to patients. Conclusion: Our survey highlights the importance of clear communication between radiologists and ED physicians when incidental findings are encountered. Radiologists play an important role in alerting ED physicians and clinicians who have access to patients' radiology reports to the presence of incidental findings including hepatic steatosis.